Identification of Proteases and Protease Inhibitors in Seeds of the Recalcitrant Forest Tree Species Quercus ilex - Escandón, Monica; Bigatton, Ezequiel D.; Guerrero-Sánchez, Victor M.; Hernández-Lao, Tamara; Rey, Maria-Dolores; Jorrín-Novo, Jesus V.; Castillejo, Maria Angeles (Frontiers in Plant Science, 2022)
Proteases and protease inhibitors (PIs) have been identified in the recalcitrant species Quercus ilex using in silico and wet methods, with focus on those present in seeds during germination. In silico analyses showed that the Q. ilex transcriptome database contained 2240 and 97 transcripts annotated as proteases and PIs, respectively, mostly represented by the serine and metallo families. The data were compared with those previously reported for other Quercus species. Changes in proteases and PIs alongside seed germination in cotyledon and embryo axis tissues were assessed using proteomics and in vitro and in gel activity assays. Shotgun (LC–MSMS) analysis in nonviable (NV), mature (T1) and germinated (T3) seeds allowed the identification of 177 proteases and 12 PIs, mostly represented by serine and metallo types. Total protease activity, as determined by in vitro assays, did not show differences among cotyledon samples, while embryo axis peaked at T4 stage. Gel assays revealed the presence of protease activities in 10 resolved bands (60-260 kDa). Bands showing quantitative or qualitative changes upon germination were observed in embryo axes at Mr values of 60-140 kDa. Shotgun analysis of the 10 bands with protease activity supported the results obtained in the overall proteome analysis, with 227 proteases and 3 PIs identified mostly represented by the serine, cysteine and metallo families. The combined use of shotgun proteomics and protease activity measurements allowed the identification of tissue-specific (e.g., cysteine protease inhibitors in embryo axes of mature acorns) and stage-specific proteins (e.g., related to mobilization of storage proteins accumulated in T3 stage). Proteins showing differences between non-viable and viable seeds could be related to viability, and those variables between mature and germinated could be associated to germination. These differences were mostly observed in embryo axes, among them those implicated in mobilization of reserve proteins, (e.g., cathepsin H and Clp proteases). Also the large number of CNS and 26S proteasome complex subunits differentially identified in embryos suggests that protein degradation plays a major role early in germination. Conversely, aspartic proteases such as nepenthesins were exclusively identified in NV seeds, so their presence could be used as indicator of nonviability.